Policies and tools for comparing and recognising VET qualifications in Europe : an overview - Symeonidis, Vasileios [Verfasser]; Blomqvist, Carita [Verfasser] (Publications Office of the European Union, 2025)
“This paper provides an overview of the policies and tools employed by EU Member States to ensure the comparability and recognition of VET qualifications. It explores the role of existing EU transparency tools, the methods used by national authorities and stakeholders to compare and recognise VET qualifications, and identifies relevant themes and concepts that could support the development of a practically oriented framework for diverse recognition purposes in Europe. The findings highlight the need for conceptual consistency, the importance of building mutual trust between national qualification systems and using learning outcomes in recognition processes, as well as the potential of digitalisation and artificial intelligence to enhance the efficiency and effectiveness of comparison and recognition processes. The paper concludes by outlining implications and actionable insights, and identifies areas for future research, emphasising the need for sustained collaboration to foster transparent and flexible recognition practices that enhance mobility and skills utilisation across the EU.” (editor; BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; 370; Qualifikation; Bildungsabschluss; Auslandsqualifikation; Anerkennung; Internationaler Vergleich; Europäische Union; Learning Analytics